2015
DOI: 10.1038/onc.2015.58
|View full text |Cite
|
Sign up to set email alerts
|

β2-AR signaling controls trastuzumab resistance-dependent pathway

Abstract: Currently, trastuzumab resistance is a major clinical problem in the treatment of Her2-overexpressing breast cancer. The underlying molecular mechanisms are not fully understood. Our previous study demonstrates that β2-adrenergic receptor (β2-AR) and Her2 comprise a positive feedback loop in human breast cancer cells and that crosstalk between Her2 and β2-AR affects the bio-behaviors of breast cancer cells, suggesting that the β2-AR activation may be involved in trastuzumab resistance. In this study, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 65 publications
2
63
0
Order By: Relevance
“…Accumulated evidence indicates that persistent secretion of stress-related hormones and neurotransmitters under chronic stress seriously affects the process of tumor development. Previous studies, including ours, demonstrated that the β2-adrenergic receptor (β2-AR), which mediates the effects of stress-related catecholamines on tumor cells [4], was overexpressed in breast and gastric cancer tissues and that crosstalk between β2-AR and oncogene receptors induced enhanced proliferation signaling in cancer cells [5][6][7]. Aberrant activation of β-adrenergic signaling promoted the growth, invasion, and metastasis of tumors [8].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Accumulated evidence indicates that persistent secretion of stress-related hormones and neurotransmitters under chronic stress seriously affects the process of tumor development. Previous studies, including ours, demonstrated that the β2-adrenergic receptor (β2-AR), which mediates the effects of stress-related catecholamines on tumor cells [4], was overexpressed in breast and gastric cancer tissues and that crosstalk between β2-AR and oncogene receptors induced enhanced proliferation signaling in cancer cells [5][6][7]. Aberrant activation of β-adrenergic signaling promoted the growth, invasion, and metastasis of tumors [8].…”
Section: Introductionmentioning
confidence: 73%
“…Additionally, the safety of β-blocker use has been demonstrated in patients with breast cancer [41]. Our previous study showed that concurrent treatment with a β-blocker and trastuzumab, a monoclonal antibody used as first-line therapy for Her2-overexpressing metastatic breast cancer, significantly improved the progression-free survival and overall survival of patients [6]. The present study demonstrated that inhibition of β-adrenergic signaling reduced the metastatic colonization of the lungs by circulating breast cancer cells, highlighting potentially beneficial effects for the early use of β-blockers in preventing lung metastasis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…ERBB2 induction of migration and invasiveness of cancer cells require the activation of small GTPases and mTORC1 signaling [2123]. We examined the activation of RhoA, Rac1 and mTORC1 signaling in miR-3622b-5p-transfected cells and control ERBB2-positive cells.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, T-DM1 has recently shown promising results in HER2 þ lung cancer (9). However, despite its significant clinical efficacy, intrinsic and acquired resistance is a major limiting factor for the therapeutic efficacy of T-DM1 (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%